Clinical profile and outcomes of adult oncological patients presented to the emergency department of a tertiary care hospital - Ali, Noman; Ahmed, Shanila; Mustahsan, Syed Muhammad; Ahmed, Fareed; Sattar, Taniya; Khan, Nadeem Ullah (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the clinical presentations, diagnosis, and outcomes of oncological patients presenting to the emergency department of a tertiary care hospital. Method: The single-centre, cross-sectional study was conducted at the emergency department of the Aga Khan University Hospital, Karachi, from January 1 to December 31, 2018, and comprised all adult patients with diagnosed solid or haematological malignancy. Demographical and clinical data was recorded from medical record files. The immediate outcomes were reported as hospitalisation or discharge from the emergency department. Data was analysed using SPSS 20. Results: Of the 320 patients, 167(52.2%) were females. Overall, 214(66.9) patients were aged 35-64 years. Most of the patients had solid organ malignancy 276(86.2%), with the most common being breast carcinoma 60(18.8%). Among haematological malignancies, B-cell lymphoma 32(10%) was the most common. The most common symptoms at presentation were vomiting 78(24.4%), fever 77(24.1%), and generalised weakness 66(20.6%). Of the total, 240(75%) patients were admitted and 80(25%) were discharged. The most common discharge diagnosis was chemotherapy-induced vomiting, followed by febrile neutropenia and malignant hypercalcemia. There were 26(10.8%) deaths among the in-patients. Conclusion: Cancer patients presented to the emergency department with diverse signs and symptoms. It is essential for physicians in the emergency department to be familiar with their presentations in order to initiate prompt and timely management plans for better clinical outcomes. Key Words: Oncology patients, Emergency department, Outcomes.